CRITICAL ANALYSIS OF DIET TECHNICIAN INTERVENTIONS IN EXAMINING EFFICACY, ADHERENCE, AND LONG-TERM HEALTH OUTCOMES IN PATIENT NUTRITION PLANS - Saleh Oshaymah Hussain Alsallum, Noorah mosleh lasloom, Nouf mansour mesfer Almutleq, Zenah Hussien Ali Alrabo, Fayez Makhfur Ali Al Sulayyim, Nader Radhi K Alanazi, Khalid Olayan M Alsharari, Mohammed Busays M Alsharari; Asmahan Abdulrahman Al Shammari, Hadi Mohammed Hadi AL Margan, Alhassan Yahya Saleh Al-Abbas, Mohammed saleh shaddad Alyami, Askar Ali Bin Saleh Alyami, Salem Muhammad Askar Al-Khadra (Chelonian Research Foundation, 2022)
This critical analysis explores the paramount influence of food service activities in patient trimesters, focusing on assessing effectiveness, adherence, and the long-term impact on patient health. The study aims to find gaps in our knowledge about diet technician interventions so that we can do a complete and thorough investigation using a research design that includes a literature review and empirical analysis. Through the study of theories and methods, this analysis hopes to yield valid recommendations that address the challenges clinicians face when it comes to treating malnutrition. Overall, it illustrates how dietitians' interventions in patient care determine whether patients improve their health status. This not only highlights the need to develop guidelines on the role of dieticians in management but also how research should be done on how nutrition can help patients reduce disease incidence. Keywords: Diet Technician, Patient Nutrition, Health Outcomes, Adherence, Efficacy.